Chemically fixed autologous feeder cell-derived niche for human induced pluripotent stem cell culture1. Issue 11 (21st March 2015) - Joddar, Binata; Nishioka, Chieko; Takahashi, Eiki; Ito, Yoshihiro
<x xml:space="preserve">Abstract</x> A newer method of hiPS culture on feeder cell-derived niche is reported in this study.